Effect of Annealing Temperature on the Crystal and Morphological sizes of Fe2O3/SiO2 Nanocomposites. Issue 1 (March 2021) - Hassan, Y M; Zaid, H M; Guan, B H; Hamza, M F; Adam, A A
Abstract: Annealing the synthesized materials at different temperatures is very significant in ensuring the complete removal of the impurities during the particle formation process. Recently, nanocomposites material has shown reasonable outcomes and performed exclusively over bare single nanoparticles (NPs) in various fields of studies. In this paper, the composite of Fe2 O3 /SiO2 nanomaterial was synthesized via a Sol-gel auto-combustion method with aid of organic precursors. The material was synthesized at various concentrations and annealed at different temperatures. Characterization of the composite material was done by analyzing crystal structures, elemental composite distributions, morphologies, and chemical compositions via X-Ray Diffraction (XRD), Energy dispersed X-ray (EDX), Field Emission Scanning Electron Microscopy (FESEM), and Fourier-Transform Infrared Spectroscopy (FTIR), respectively. The chemical interaction between amorphous silica and iron oxide nanoparticles has been established due to the manifestation of the characteristic wavelengths corresponding to the linkage bond between the amorphous silica and iron oxide nanoparticles. The FESEM imaging revealed that the morphological size increased significantly with an increase in temperature. Furthermore, in the XRD experiment, it was found that increasing the temperature has significantly improved the crystal properties of the composite material. Hence, annealing temperature can serve as a reliable method that can control the morphological size and crystal structure of the materials